Indigenous Peoples' Rights Act (IPRA) Law in the Philippines: A Scoping Review on the Effectiveness - Ampater, Althea Marie; Dompor, Steven Lance; Duhac, Jenny Lyn; Paje, Bhea (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
This article reviewed the effectiveness of the Indigenous Peoples' Rights Act (IPRA) in the Philippines, from the literatures. Drawing on 50 carefully selected publications, the review highlights the theoretical and methodological frameworks employed in existing research, including qualitative and quantitative approaches. The findings reveal that while IPRA provides a legal framework for Indigenous rights, its implementation is often hindered by conflicting laws, external pressures, and a lack of alignment with the collective nature of ancestral land ownership. The review systematically categorizes the literature based on themes such as displacement, environmental degradation, and the role of government in Indigenous rights advocacy. It identifies significant barriers to effective implementation, including socio-political dynamics and the influence of development projects. This synthesis of literature not only contributes to the understanding of IPRA's impact but also serves as a foundation for future research aimed at improving policy frameworks and practices that support Indigenous communities in the Philippines. The results and discussions section will further elaborate on these themes, providing insights into the ongoing struggles and potential pathways for advancing Indigenous rights within the national legal framework.